Dialog Antar Umat Beragama Dalam Agama Katolik (Analisis Terhadap Pemikiran Franz Magnis Suseno) - Andika, Andika; Halim, Abdul; Mubarak, Zaki (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2024)
This research aims to describe the concept of dialogue between religious communities based on culture. Franz Magnis Suseno, a Catholic theologian in Indonesia has unique thoughts about building dialogue between religious communities based on culture which has implications for strengthening religious identity and multiculturalism. In analyzing the problems above, this research uses a qualitative approach through literature study. The results of this research show that the theological and cultural-based concept of inter-religious dialogue built by Franz Magnis Suseno is motivated by the spirit of culturation which is divided into three concepts, namely the concept of inculturation dialogue, interiority dialogue, and integral dialogue. This research concludes that the concept of dialogue between religious communities based on theology and culture is relevant in building harmonious religious life in Indonesia.